Pengaruh Sinbiotik Kefir Tepung Pisang Batu (Musa balbisiana) terhadap Kadar Kolesterol Total dan Kadar Trigliserida Tikus Model Sindrom Metabolik - Diana Martha Ariesta Sari; Taufik Maryusman; Santi Herlina (Universitas Islam Negeri Walisongo Semarang, 2020)
This study was conducted to analyze the effects of banana (Musa balbisiana) flour kefir synbiotic on total cholesterol level and triglyceride level of Metabolic Syndrome rats model. This research used a true experimental method with pre-post test control group design. The number of 24 rats model were randomly divided into four groups, i.e. K– (healthy rats, standard diet), K+ (Metabolic Syndrome rats, standard diet), PI (Metabolic Syndrome rats, standard diet and synbiotic 1,8 ml/200grBW/day), and PII (Metabolic Syndrome rats, standard diet and synbiotic 3,6 ml/200grBW/day), with intervention duration of 3 weeks. Blood draws were carried out at the beginning and end session of the intervention to analyze total cholesterol and triglyceride levels. The data from the measurement of total cholesterol and triglyceride levels before and after the intervention were then analyzed using the Paired T-Test. The results of the Paired T-Test showed differences (p